A role for UNEP's Regional Seas Programme under the post-2020 global biodiversity framework. (February 2022) - Ferreira, Maria Adelaide; Barrio Froján, Christopher; Gunn, Vikki; Johnson, David E.
Abstract: A case is put forward to make best use of UNEP's Regional Seas Programme (RSP) for the Convention on Biological Diversity's (CBD) post-2020 global biodiversity framework (GBF). A review of the work of the RSP's component Regional Seas Conventions and Action Plans (RSCAPs) highlights their potential for strengthening the marine and regional outlook of the GBF, as well as their current limitations. Recommendations are made to the CBD, the UNEP-RSP, its RSCAPs and to their member Parties/States to foster and further develop their mutually reinforcing roles in supporting a regional marine biodiversity dimension. Graphical Abstract: ga1 Highlights: The global biodiversity framework (GBF) needs to strengthen regional marine elements. UNEP's Regional Seas Programme (RSP) can play a key role in the post-2020 GBF. The RSP offers a legal framework to tackle common regional marine ecosystem issues. RSP's Regional Seas Conventions and Action Plans (RSCAPs) are not a homogenous group. Recommendations are made to help RSCAPS maximise their potential to support the GBF.